Independent Block of Macha Caporal: The Challenges and Restrictions in Female Dancing - Santana, Pamela (Ethnographica et Folkloristica Carpathica, 2021)
This paper explores the experience of six Macha Caporal dancers belonging to an independent female block in La Paz, a recent and still unexplored mode of association to dance. This article analyzes and makes visible the challenges and restrictions women face in endeavoring to sustain an independent dance practice in the context of urban folk dance in Bolivia. Through the accounts of the women and the ethnographic material gathered from fieldwork in 2018 in Bolivia, the study portrays the women’s dancing context revealing the challenges and restrictions linked to the condition of being women in a society that is traversed by chauvinism. In the task of dancing, the women’s performance reveals a complex negotiation of gender roles, ideas, and expectations; processes that highlight the women’s agency and determination to carry on with a practice that ultimately grants them feelings of self-validation and autonomy.